THE EFFECT OF MOTHER'S READINESS ON BREASTFEEDING SUCCESS - Nurmeyda Lentina; Risa Etika; Dwi Izzati Budiono (Universitas Airlangga, 2021)
Abstract Background: The practice of breastfeeding in Indonesia is not 100% carried out. The data stated that in 2017 children aged <6 months who were exclusively breastfed were around 52%. This figure is considered low and below the national target (80%). One of the important key holders of successful breastfeeding is the mother's readiness to breastfeed. Mothers can prepare starting from knowledge of exclusive breastfeeding. In order to be able to carry out mature exclusive breastfeeding, preparation for lactation since pregnancy is an important factor. Considering that the mother's readiness is still low, it is important to conduct research on this readiness factor. This study aims to analyze the effect of mother's readiness on breastfeeding success. Methods: This research uses analytical observational with cross sectional approach. The sample used was 100 babies according to the specified criteria. The data collection technique was done by filling out online questionnaires. The data were then analyzed using the Chi Square test. Results:  This study shows the effect of mothers readiness with breastfeeding success which obtained a p value of 0.045. the results of the chi square test showed that mother's readiness = 0.045 (α < 0,05), mother's knowledge = 0.005 (α < 0,05) and lactation preparation = 0.19 (α < 0,05). Conclusion: These data indicate that there is an influence of mother's readiness on breastfeeding success.